2022
DOI: 10.1097/fjc.0000000000001205
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in Low-Density Lipoprotein Cholesterol Reduction With PCSK9 Inhibitors in Real-world Patients: The LIPID-REAL Registry

Abstract: Background:Previous evidence supports that monoclonal antibodies that inhibit the proprotein convertase subtilisin/kexin type 9 (PCSK9) reduce low-density lipoprotein cholesterol (LDLc) by 50%–65%, regardless of baseline treatments. We tested possible sex differences in a multicentre registry of real-world patients treated with PCSK9 inhibitors.Methods:This is a multicentre and retrospective study of 652 patients initiating treatment with any PCSK9 inhibitor in 18 different hospitals. Before-treatment and on-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 35 publications
1
13
1
Order By: Relevance
“…Recent data have shown similar cardiovascular benefits in both sexes using plasma proprotein convertase subtilisin/kexin type 9 inhibitors (iPCSK9) 23 , although the LIPID-REAL Registry 24 has shown lower LDL-c reduction in women in the 2 highest quartiles. Nevertheless, the study on the use of iPCSK9 in Catalonia (Spain) from the Catalan Department of Health observed that women only received 41% of a total of 1.917 provided treatments 25 .…”
Section: Discussionmentioning
confidence: 99%
“…Recent data have shown similar cardiovascular benefits in both sexes using plasma proprotein convertase subtilisin/kexin type 9 inhibitors (iPCSK9) 23 , although the LIPID-REAL Registry 24 has shown lower LDL-c reduction in women in the 2 highest quartiles. Nevertheless, the study on the use of iPCSK9 in Catalonia (Spain) from the Catalan Department of Health observed that women only received 41% of a total of 1.917 provided treatments 25 .…”
Section: Discussionmentioning
confidence: 99%
“…This is an investigator-initiated study of patients treated with PCSK9 inhibitors under local criteria. 14,15 It is a multicenter and retrospective study designed to assess the efficacy of PCS9 inhibitors treatment on LDLc reduction in real-world patients. Investigators were invited to participate and share their results using a simple database designed by the study and investigators from 18 different Spanish hospitals finally agreed to participate; all were included in the public national health system.…”
Section: Methodsmentioning
confidence: 99%
“…This is an investigator‐initiated study of patients treated with PCSK9 inhibitors under local criteria 14,15 . It is a multicenter and retrospective study designed to assess the efficacy of PCS9 inhibitors treatment on LDLc reduction in real‐world patients.…”
Section: Methodsmentioning
confidence: 99%
“…As for PCSK9 inhibitors, data from the FOURIER trial demonstrated that inhibition of PCSK9 with evolocumab on a background of statin therapy lowered LDL-C levels in all subgroups with no sex differences [84]. However, only one multicenter registry investigated sex-related differences in PCSK9 inhibitors' efficacy [85]. The study demonstrated that women had substantially higher LDL-C levels and a lower LDL-C reduction compared with men (47.4% vs. 56.9%; P = 0.0002) [85].…”
Section: Pharmacological Strategiesmentioning
confidence: 99%
“…However, only one multicenter registry investigated sex-related differences in PCSK9 inhibitors' efficacy [85]. The study demonstrated that women had substantially higher LDL-C levels and a lower LDL-C reduction compared with men (47.4% vs. 56.9%; P = 0.0002) [85].…”
Section: Pharmacological Strategiesmentioning
confidence: 99%